S SIMULASI BENCANA PADA MAHASISWA KEPERAWATAN DALAM UPAYA PENINGKATAN PENGETAHUAN PENANGGULANGAN BENCANA KEBAKARAN - Elfi Quyumi Rahmawati; Erna Susilowati (LPPM Universitas Sari Mulia, 2020)
Background: Fire is a form of disaster, both natural and complex. Fire can cause material losses that have the potential to cause death so that it requires attention to the safety of residents of residential areas. Objective: to determine the knowledge of nursing students on fire emergency management with a disaster simulation approach. Method: pre experimental design research with one group pre test post test with cross sectional design, sample size 30 students level 1 and 2 at Akper Dharma Husada Kota Kediri, with simple random sampling method with data analysis using t test analysis on SPSS. Knowledge data before and after following the simulation of fire emergency management obtained from filling out questionnaires to respondents.Results: the study showed a p value of 0.000 which indicates the effect of fire emergency simulation on increasing knowledge.Conclusion: fire emergency disaster simulation activities have a significant effect on changes in knowledge of nursing students.